Toenail manganese as a potential biomarker for in utero and early childhood exposure studies. Issue 1 (December 2018) - Cigan, Shannon; McGovern, Patricia; Choudhary, Kriti; Miller, Neely; Georgieff, Michael; Rao, Raghavendra; Stepanov, Irina
Abstract Elevatedin utero and early childhood exposure to manganese may have adverse effects on neurodevelopment. We conducted preliminary analyses to evaluate toenails as a matrix for investigating manganese exposure in infants. Infant and maternal toenail and hair samples were collected from 25 infants (7 months old) and their mothers. A subset of mothers was recruited in the third trimester of pregnancy and some also provided pre-natal toenail, hair, and blood samples, cord blood, and additional post-natal samples. Collected samples were analyzed by inductively coupled plasma mass-spectrometry. Toenail manganese levels in infants ranged from below the limit of detection (LOD) to 2.80 µg/g. Only 1 toenail sample and 4 hair samples contained levels of manganese below LOD. Associations between infant and maternal biomarkers were not statistically significant. Analysis of multiple post-natal toenail samples from a single infant-mother pair showed an increase in the infant's toenail manganese and a decrease in maternal toenail manganese over the first year of the infant's life. Overall, our findings suggest that toenails may serve as a valuable biological matrix for measuring manganese exposure in newborns and infants; however, additional studies are needed to determine the impact of the timing of toenail sample collection on its utility in assessing early life exposure and health outcomes.